Necrotizing Bronchitis with Airway Obstruction Due to Macrolide-Resistant Mycoplasma pneumoniae in a Child: A Case Report - Li Z; Xu Y; Xiang Y (Infection and Drug Resistance)
Zhongjie Li,* Yao Xu,* Yujian Xiang* Department of Pediatrics, Zhejiang University School of Medicine Second Affiliated Hospital Jiashan Branch, the First People’s Hospital of Jiashan, Jiashan, Zhejiang, 314100, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zhongjie Li, Department of Pediatrics, Zhejiang University school of medicine second Affiliated Hospital Jiashan Branch, The first People’s Hospital of Jiashan, No. 1218 Tayo South Road, Jiashan, Zhejiang, 314100, People’s Republic of China, Email lizhongjie52@dingtalk.comAbstract: Although infection with Mycoplasma pneumoniae is generally self-limited, it may cause refractory or life-threatening pneumonia with pulmonary or extrapulmonary complications. Necrotizing bronchitis is a rare condition with a high mortality rate. The present report describes a patient with mycoplasma pneumonia and necrotizing bronchitis that caused airway obstruction. A 7-year-old girl presented with fever and cough and was hospitalized. Her symptoms did not improve, and mild hypoxemia was observed. Fiberoptic bronchoscopy revealed diffuse bronchitis with necrotic and hemorrhagic material obstructing the bronchus. The necrotic tissue was removed directly, unblocking the airways. This case underscores the importance of fiberoptic bronchoscopy for early diagnosis and treatment of severe respiratory complications associated with Mycoplasma pneumoniae infection, such as necrotizing bronchitis. Early recognition and timely intervention are critical to improving patient outcomes in such cases.Keywords: Mycoplasma pneumoniae, necrotizing bronchitis, bronchial fiberscope, airway obstruction